A comprehensive environmental assessment of petrochemical solvent production - Capello, Christian; Wernet, Gregor; Sutter, Jürgen; Hellweg, Stefanie; Hungerbühler, Konrad (The international journal of life cycle assessment, 2009)
Background, aim, and scope Organic solvents are used in large quantities in the chemical, metal and electronics industries as well as in many consumer products, such as coatings or paints, and are therefore among the most important chemicals. The petrochemical production of organic solvents is a relevant environmental issue because fossil resources are needed (crude oil and natural gas), synthesis processes are energy-intensive and cause considerable amounts of emissions. So far, comprehensive data on the environmental impact are rather scarce. The aim of this paper is to therefore present a systematical environmental assessment of the main petrochemical solvent production routes using the Life Cycle Assessment (LCA) method. Methods Fifty organic solvents were selected covering the most important representatives from the various chemical groups (e.g., alcohols, esters, ketones). To conduct the LCA, 40 new Life Cycle Inventories (LCI) were established and existing LCI were improved. The petrochemical solvent production was structured into four production routes. In these production routes, the single chemical unit processes (e.g. esterification, carbonylation or hydrogenation) were analyzed in order to determine characteristic environmental impacts. Results and discussion The four solvent production routes including the unit processes and intermediates are presented. Additionally, energy profiles of these production routes are shown using the Cumulative Primary Energy Demand (CED) as an indicator for the environmental impact. The results were cross-checked with the Global Warming Potential and the Eco-indicator 99 method and good correlations were found. Processes that show high environmental impacts are the dehydration of butylene glycol to tetrahydrofuran, the carbonylation of methanol to methyl formate, the hydrogenation of acetone to methyl isobutyl ketone, and the Reppe synthesis of formaldehyd/acetylene to butylene glycol. Based on the energy profiles, ranges of environmental impacts are determined for all unit processes. On the one hand, esterification and alkylation processes cause high CED values because complex ancillaries are needed and hydroformylation and carbonylation processes are energy-intensive. On the other hand, in hydration, hydrogenation, hydrolysis, and oxidation processes, ancillaries with low CED are added to the chemical structure that result in low CED ranges for these unit processes. Dehydrogenation and molecular sieve separation processes seem to be energy efficient and no ancillaries are required. Therefore, these unit processes cause the lowest CED values. Perspectives Subject of further research in this field should be the environmental analysis of further process steps that include the presented unit processes and a subsequent statistical analysis in order to derive reliable data ranges for all unit processes. Such statistically robust ranges could be used in the approximation of missing life-cycle inventory data of other chemical products and intermediates.